First Person: Everywhere, like Jerusalem, the ground is burning: On teaching in a time of conflict. (October 2019) - Moses, Danial Noah
For nearly 20 years, Daniel Noah Moses has worked with educators to promote dialogue and understanding in some of the world's most violent conflict zones, such as Israel/Palestine, Armenia, and Pakistan. Now, after moving back to the United States, he finds that tensions are soaring in the U.S. as well. For the first time, he writes, it strikes him that American educators can relate to the challenges facing teachers in global hotspots .